b-glucosidase Producing Bacillus Isolated from Thua-nao, an Indigenous Fermented Soybean Food in Thailand - Nutwara Meannui (Science Faculty of Chiang Mai University, 2019)
The characteristics of commercial dried flatten Thua-nao collected from Northern of Thailand, namely oven dried (LPO) and sun dried (LPS) samples from Lamphun, sun dried sample from Chiang Mai (CMS) and sun dried sample from Chiang Rai (CRS),were investigated. The variations of chemical and physical characteristics were found among these Thua-nao products. Seventeen isolates of spore-forming bacteria were obtained from such products. Among these, four isolates (LPO-2, LPO-4, LPS-2 and CMS-1) were identified as Bacillus subtilis group by API 50CHB kit. For cellulolytic enzyme production, CMS-1 exhibited the highest clear zone on tryptic soy agar supplemented with carboxymethyl cellulose (P<0.05). Contrastingly, LPO-2 had the highest b-glucosidase activity with the lowest clear zone of cellulolytic enzyme activity (P<0.05). From 16S rRNA gene sequencing result, LPO-2 could be identified as Bacillus sp. and closely related to B. subtilis group.